The Regulation of Entry - Djankov, Simeon; La Porta, Rafael; Lopez de Silanes, Florencio; Shleifer, Andrei (World Bank, Washington, DC, 2014)
The authors present new data on the regulation of the entry of start-up firms in 85 countries. The data cover the number if procedures, official time, and official costs that a start-up firm must bear before it can operate legally. The official costs of entry are extremely high in most countries. Countries that regulate entry more heavily have greater corruption and larger unofficial economics, but not better quality goods (public or private). Countries with more democratic and limited governments regulate entry more lightly. The evidence is inconsistent with public interest theories of regulations, but supports the public choice view that regulating entry benefits politicians and bureaucrats.